2008
DOI: 10.1083/jcb.200802025
|View full text |Cite
|
Sign up to set email alerts
|

ODA16 aids axonemal outer row dynein assembly through an interaction with the intraflagellar transport machinery

Abstract: Formation of flagellar outer dynein arms in Chlamydomonas reinhardtii requires the ODA16 protein at a previously uncharacterized assembly step. Here, we show that dynein extracted from wild-type axonemes can rebind to oda16 axonemes in vitro, and dynein in oda16 cytoplasmic extracts can bind to docking sites on pf28 (oda) axonemes, which is consistent with a role for ODA16 in dynein transport, rather than subunit preassembly or binding site formation. ODA16 localization resembles that seen for intraflagellar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
179
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(188 citation statements)
references
References 35 publications
8
179
0
1
Order By: Relevance
“…As IFT46 interacts at least with ODA16, IFT88, IFT81, IFT74, IFT70 and IFT52 (Ahmed et al, 2008;Fan et al, 2010;Lucker et al, 2005Lucker et al, , 2010Taschner et al, 2011Taschner et al, , 2014, we next determined whether the basal body localization of IFT46 is dependent on other IFT components. If so, this typical accumulation will be abolished in corresponding null mutants.…”
Section: Ift46-c1 Is Assembled Into the Ift Machinerymentioning
confidence: 99%
“…As IFT46 interacts at least with ODA16, IFT88, IFT81, IFT74, IFT70 and IFT52 (Ahmed et al, 2008;Fan et al, 2010;Lucker et al, 2005Lucker et al, , 2010Taschner et al, 2011Taschner et al, , 2014, we next determined whether the basal body localization of IFT46 is dependent on other IFT components. If so, this typical accumulation will be abolished in corresponding null mutants.…”
Section: Ift46-c1 Is Assembled Into the Ift Machinerymentioning
confidence: 99%
“…Recent data have demonstrated that the loading of specific cargo proteins might require specific IFT-particle subunits. For instance, IFT46 and an associated adaptor protein, ODA16, are essential for transporting outer-arm dynein along C. reinhardtii axonemes (Ahmed et al, 2008;Hou et al, 2007). In the case of membrane-protein cargos, it has been observed that mutations in heterotrimeric kinesin-II lead to defects in the transport of opsin and arrestin from the inner to the outer segment in the mouse photoreceptor (Marszalek et al, 2000).…”
Section: Ift Cargosmentioning
confidence: 99%
“…Other axonemal components known to travel by IFT in Chlamydomonas are the nexin–dynein regulatory complex proteins DRC2 and DRC4 and the central pair protein PF16 (Wren et al , 2013). Outer dynein arms (ODAs) are also likely cargoes for IFT via interaction with IFT46 through the adaptor protein ODA16 (Hou et al , 2007; Ahmed et al , 2008). Several subunits of the BBSome, a cargo adapter for membrane proteins, have also been demonstrated to move by IFT (Blacque et al , 2004; Lechtreck et al , 2009a) as have several integral and associated membrane proteins (Qin et al , 2005; Huang et al , 2007).…”
Section: Introductionmentioning
confidence: 99%